Morphometric parameters as risk factors for anterior cruciate ligament injuries – A MRI case-control study - Stijak, Lazar; Bumbaširević, Marko; Kadija, Marko; Stanković, Gordana; Herzog, Richard; Filipović, Branislav (Vojnosanitetski pregled, 2014)
Background/Aim. The anterior cruciate ligament (ACL) is the most frequently injured ligament of the knee, representing 50% of all knee injuries. The aim of this study was to determine the differences in the morphometry of knee injury patients with an intact and a ruptured anterior cruciate ligament. Methods. The study included 33 matched pairs of patients divided into two groups: the study group with the diagnosis of anterior cruciate ligament rupture, and the control group with the diagnosis of patellofemoral pain but no anterior cruciate ligament lesion. The patients were matched on the basis of 4 attributes: age, sex, type of lesion (whether it was profession-related), and whether the lesion was left- or right-sided. Measurements were carried out using magnetic resonance imaging (MRI). Results. The anterior and posterior edges of the anterior cruciate ligament in the control group were highly significantly smaller (p
Keywords: anterior cruciate ligament; injuries; risk factors; anthropometry